2012
DOI: 10.1088/0004-637x/756/1/76
|View full text |Cite
|
Sign up to set email alerts
|

GAS EMISSIONS IN PLANCK COLD DUST CLUMPS—A SURVEY OF THEJ= 1-0 TRANSITIONS OF12CO,13CO, AND C18O

Abstract: A survey toward 674 Planck cold clumps of the Early Cold Core Catalogue (ECC) in the J=1-0 transitions of 12 CO, 13 CO and C 18 O has been carried out using the PMO 13.7 m telescope. 673 clumps were detected with the 12 CO and 13 CO, and 68% of the samples have C 18 O emission. Additional velocity components were also identified. A close consistency of the three line peak velocities was revealed for the first time. Kinematic distances are given out for all the velocity components and half of the clumps… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
119
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(133 citation statements)
references
References 64 publications
13
119
1
Order By: Relevance
“…These observations by Wu et al (2012) are a good opportunity to check whether the data from the survey of Dame et al (2001) can be associated with our higher resolution Herschel data, despite the low spatial resolution (∼7 arcmin) and the poor spatial sampling of the survey. Figure 2 shows that the agreement between the two sets of observations is generally within the error bars.…”
Section: Kinematic Distancesmentioning
confidence: 94%
See 3 more Smart Citations
“…These observations by Wu et al (2012) are a good opportunity to check whether the data from the survey of Dame et al (2001) can be associated with our higher resolution Herschel data, despite the low spatial resolution (∼7 arcmin) and the poor spatial sampling of the survey. Figure 2 shows that the agreement between the two sets of observations is generally within the error bars.…”
Section: Kinematic Distancesmentioning
confidence: 94%
“…Among our fields, 38 are covered by the fully sampled part of the survey, 57 by the partially sampled part, and 21 are not covered at all. Wu et al (2012) observed the J = 1−0 CO line towards 674 Planck clumps using the Purple Mountain Observatory 13.7 m telescope. Only 44 of our fields host sources observed by these authors.…”
Section: Other Datamentioning
confidence: 99%
See 2 more Smart Citations
“…The effects of young intermediate-mass stars on the environment are conspicuous in L1340 B. The wispy structure of the 8 μm emission, the bowshock-like structure associated with an A2-type star, and the double-peaked CO lines at the positions of the Planck Cold Clumps (Wu et al 2012) associated with L1340 suggest violent swirling of the gas in this region. The low surface density of YSOs, compared to the other clumps of the cloud, indicates that the prestellar gas in L1340 B had higher temperature and lower density than in L1340 A and L1340 C, owing to the heating from the ambient B-type stars.…”
Section: Star Formation In L1340mentioning
confidence: 98%